Influence of incubation temperature on embryo development, hatchling morphology and early growth rate in red-footed tortoise (Chelonoidis carbonaria) - Mendoza, Pierina [UNESP]; Cerdan, Isaura [UNESP]; Garcia, Beatriz [UNESP]; Furuta, Camila [UNESP]; Di Santo, Ludmilla [UNESP]; Sanfilippo, Luiz F.; Bícego, Kênia C. [UNESP]; Carciofi, Aulus C. [UNESP] (Elsevier, 2021)
Reptile embryos respond to temperature changes with metabolic and physiological adjustments that influence hatchling success, phenotype, behaviour, and growth rate. Climate change and global warming can affect the reptile population by altering the frequencies of hatchling survival and phenotypes. Therefore, previous studies proposed artificial incubation as a potential strategy for mitigating these effects. Red-footed tortoise (Chelonoidis carbonaria) eggs were collected and incubated at constant temperatures of 27.5 °C and 29.5 °C to investigate the physiological effects of temperature on embryo development, hatchling morphology, and early post-hatch growth rate. The direct effect of temperature on the incubation period, egg mass loss, hatching success, hatchling size, and mass was evaluated at hatching and three months of age. Hatchlings from 29.5 °C presented a shorter incubation period (141 days) than those from 27.5 °C (201 days; p < 0.05). Egg mass loss, hatchling mass, and size at hatching were not different between the incubation temperatures (p > 0.05). However, the hatching success (survival rate) was lower (64.5% versus 100%) in eggs incubated at 29.5 °C, but the hatchling mass and straight plastron width were higher at three months of age than those from eggs incubated at 27.5 °C (p < 0.05). These results indicate that incubation temperature influences hatching success and hatchling size and mass in the first months by influencing the early growth rate.
Keywords: Chelonian; Egg incubation; Hatchling growth; Ovoscopy; Thermal effect